2006
DOI: 10.1111/j.1748-5827.2006.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival in a retrospective cohort of 28 dogs with insulinoma

Abstract: Survival times in this study exceed those in other studies published previously. In part, this is explained by an improved remission duration following surgery compared with previous reports. More striking though is the longevity of patients following institution of medical therapy. These data give strong objective support to the role of medical therapy in the management of canine insulinoma, including following relapse after surgically induced remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
142
2
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(164 citation statements)
references
References 10 publications
10
142
2
10
Order By: Relevance
“…Depending on the study, the sensitivity of conventional ultrasonography for detecting pancreatic insulinomas is 28-75% in dogs. 4,[29][30][31][32] In a case series of 14 dogs with insulinomas, CT showed a higher sensitivity for detecting insulinoma mass lesions than that of conventional ultrasonography. 4 In humans, the sensitivity of transabdominal ultrasonography for localizing pancreatic insulinomas is 9-64%.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the study, the sensitivity of conventional ultrasonography for detecting pancreatic insulinomas is 28-75% in dogs. 4,[29][30][31][32] In a case series of 14 dogs with insulinomas, CT showed a higher sensitivity for detecting insulinoma mass lesions than that of conventional ultrasonography. 4 In humans, the sensitivity of transabdominal ultrasonography for localizing pancreatic insulinomas is 9-64%.…”
Section: Discussionmentioning
confidence: 99%
“…Our present series of carcinomas included 3 cases without metastases (clinical stage 1), 2 cases of carcinoma with metastasis to associated lymph nodes at surgery (clinical stage 2), and 3 cases with hepatic metastases (clinical stage 3). All cases were within the 95% confidence interval of median survival times for insulinoma in each clinical stage as reported in another recent retrospective study [15].…”
Section: Discussionmentioning
confidence: 99%
“…For the treatment of canine insulinoma, the efficacy of medical treatments after surgery has been suggested [4,15], but surgical treatment after clinical diagnosis remains the treatment of choice [4,13,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ki67 is a proliferation marker expressed during the active phases of the cell cycle and absent in resting cells (Scholzen and Gerdes, 2000). Polton, et al, (2007) reported a median disease free interval of 496 days (95% CI: 302 to 690 days) in 19 dogs that underwent partial pancreatectomy. Tobin and colleagues (1999) reported median survival time after diagnosis of 74 days (range, 8 to 508 days) and 381 days (range, 20 to 1758) in dogs treated medically versus dogs that initially underwent surgery followed by medical treatment, respectively.…”
Section: Prognosismentioning
confidence: 99%